Research on optimisation of e-commerce supply chain logistics management mode under blockchain technology - Guo, Suyao (Transactions on Economics, Business and Management Research, 2024)
The introduction of blockchain technology in e-commerce supply chain logistics management can effectively improve the operation effect. The problems existing in the current e-commerce supply chain logistics management mode are analysed on the basis of an overview of blockchain technology, and then the feasibility of e-commerce supply chain logistics management mode under blockchain technology is explored. The study concludes that: blockchain technology has distributed bookkeeping characteristics, which can effectively solve the problem of information asymmetry in the e-commerce supply chain, and the programmable contract in the blockchain can match all the information in the process of payment and transaction of e-commerce supply chain, identify the responsibility of the transaction, realise the traceability of the goods, and reduce the risk of the transaction. Based on the conclusion of the study, the countermeasures of using blockchain technology to improve e-commerce supply chain logistics, optimizing logistics management with the concept of "blockchain + Internet of Things", and solving the problems of the traditional management mode with "blockchain + supply chain" finance are proposed.